(untitled) (LACCEI, 2024)
The growth of the construction industry has allowed the development of new methodologies to improve productivity and project management. Over the years, large companies have mitigated variability in their process workflows by adopting best practices. For this reason, a collaborative management method is developed to reduce internal variability in construction projects. To do this, based on the literature review, a preliminary four-stage method is proposed, with the aim of establishing a flowchart that allows reducing variability by adopting collaborative management tools. This preliminary method is put to evaluation through an expert judgment to verify the reliability and reliability of the questions. Likewise, a focus group is developed to establish improvements in the management tools used in each stage of the method. After evaluating and filtering the preliminary method by professionals with knowledge in project management, the final version of the collaborative management method was obtained with the modifications proposed by experts on the subject. Finally, the results obtained indicated that the final method is reliable to reduce internal variability in construction projects, establishing processes through a flowchart, which are supported by collaborative management tools.